Antimicrobial resistance in the globalized food chain: a One Health perspective applied to the poultry industry - de Mesquita Souza Saraiva, Mauro [UNESP] (2022)
Antimicrobial resistance (AMR) remains a major global public health crisis. The food animal industry will face escalating challenges to increase productivity while minimizing AMR, since the global demand for animal protein has been continuously increasing and food animals play a key role in the global food supply, particularly broiler chickens. As chicken products are sources of low-cost, high-quality protein, poultry production is an important economic driver for livelihood and survival in developed and developing regions. The globalization of the food supply, markedly in the poultry industry, is aligned to the globalization of the whole modern society, with an unprecedented exchange of goods and services, and transit of human populations among regions and countries. Considering the increasing threat posed by AMR, human civilization is faced with a complex, multifaceted problem compromising its future. Actions to mitigate antimicrobial resistance are needed in all sectors of the society at the human, animal, and environmental levels. This review discusses the problems associated with antimicrobial resistance in the globalized food chain, using the poultry sector as a model. We cover critical aspects of the emergence and dissemination of antimicrobial resistance in the poultry industry and their implications to public health in a global perspective. Finally, we provide current insights using the multidisciplinary One Health approach to mitigate AMR at the human-animal-environment interface.